Influence of Framing Effect on Consumers’ Purchase Intention of Artificial Meat—Based on Empirical Analysis of Consumers in Seven Cities - Shan, Lijie; Jiao, Xinli; Wu, Linhai; Shao, Yingcheng; Xu, Lingling (Frontiers in Psychology, 2022)
Artificial meat is a type of food that has emerged in recent years. It is similar in shape, color, and taste to meat. Its market scale is developing rapidly, and its future development prospect is bright. To explore Chinese consumers' purchasing intention regarding artificial meat products, this study used the framing effect theory to analyze the differences in consumers' purchasing intentions under different information frames based on the survey data of 6,906 consumers from seven cities in China. Hierarchical regression and variance analysis explored the moderating effects of consumers' product knowledge level and health motivation on the frame effect. The results show that consumers' purchase intention under the positive information frame is significantly higher than that under the negative information frame. Consumers with higher product knowledge levels have higher purchase intention under the positive information frame, whereas consumers with lower health motivation have lower purchase intention under the two information frames. The government and relevant enterprises should focus on promoting positive information about artificial meat products, improving consumers' cognition level of artificial meat products, guiding consumers to form a scientific diet concept to enhance their purchase intention of artificial meat products, and promoting the healthy development of the artificial meat industry.